Efektivitas Pembelajaran Berbasis Masalah Terhadap Pemahaman Konsep dan Kemampuan Berpikir Tingkat Tinggi Siswa Pada Materi Fungsi Kuadrat di Kelas X SMK Swasta Parulian 1 Medan T.A 2025/2026 - simarmata, eunike claudia; Tambunan, Hardi; Simanjuntak, Ruth Mayasari (Universitas PGRI Semarang, 2026)
This study aims to determine the effectiveness of problem-based learning on students’ conceptual understanding and higher-order thinking skills regarding quadratic functions among 10th-grade students at Parulian 1 Private Vocational High School in Medan during the 2025/2026 academic year. This is a quantitative study using a descriptive approach. The population in this study consists of all 10th-grade students, while the sample comprises Class X-TKJ and X-AP, selected through purposive random sampling. The instruments used include essay tests, questionnaires, and observation sheets, all of which have been validated for validity and reliability. The results of the study indicate that problem-based learning is effective in improving students’ conceptual understanding of mathematics and higher-order thinking skills, with a level of effectiveness falling into the moderate category.